The influence of psycho-emotional arousal on the cardiological indicators of NANGU cadets during a training simulation of the execution of a combat task using augmented reality technologies - Chala , Sofia; Lutsak, Olena; Hrynzovskyi , Anatolii; Chernenko, Lyudmila; Kalashchenko, Svitlana; Fedosov, Yuriy; Drapey, Ihor; Martynenko, Serhii; Boyko, Yuliia; Chayka, Yuriy (The Ukrainian Scientific Medical Youth Journal, 2022)
today, in the conditions of military operations on the territory of Ukraine, the need for training cadets of higher military educational institutions (MEIs) for the successful performance of various combat tasks. The readiness of cadets to perform these tasks in conditions of significant psycho-emotional, nervous and physical stress is growing. The best way to achieve the maximum level of willingness of cadets of MEIs is to conduct a training simulation of the performance of a combat mission. However, the analysis of the technical and special training of the combat vehicle teams indicates an insufficient level of training for the crews, which does not ensure the full performance of combat tasks. During the educational process, not enough time is devoted to training on training equipment. We regarded it relevant to consider the issue of assessing the cardiological indicators of cadets when performing training simulations of a combat task for a better selection of people. This category of human has to carry out their professional activities in conditions of chronic stress and constant risk to their lives and health. The purpose of our work is to obtain and analyze the monitoring data of the basic parameters of the heart in the category of healthy men aged 18-21 years who are studying at the National Academy of the National Guard of Ukraine (NANGU). Also, we need to evaluate the cardiological parameters of tolerance during a training simulation of the performance of a combat task. 88 cadets of the 3rd and 4th years of NANGU were examined. The study did not include cadets with existing chronic diseases in the exacerbation phase, who had acute respiratory infections, signs of psycho-emotional overload, aged less than 18 years, and those who refused the examination. We used the BTR-4E training complex equipped with the Parus combat module to simulate a combat mission. The response of the cardiovascular system of cadets to the training load is characterized by a statistically significant (p=0.025) increase in the amplitude of T peaks, a decrease in the amplitude of P peaks (p<0.001), and a reduction in heart rate (p<0.001) when measurements are taken immediately after the end of the exercise. We have established that relaxation and rapid recovery of cardiac parameters to values characteristic of a state of rest occur 1-3 minutes after the completion of a training simulation of the performance of a combat task. It indicates that using immersive technologies (in our case, augmented reality technologies) positively affects autonomic regulation in cadets.